2002
DOI: 10.1017/s0012162201002870
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal Doppler assessment of cerebral blood flow velocity in healthy preterm and term infants

Abstract: The aim of the present study was to generate normal reference data for anterior and middle cerebral artery blood flow velocity and resistance index in preterm and term infants during the first 8 hours of life. The study population longitudinally included 120 healthy preterm and term infants (gestational age 24 to 41 weeks), all of appropriate weight for gestational age. The following parameters were studied: peak-systolic velocity, end-diastolic velocity, mean velocity, and resistance index. All parameters wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
0
17
1
1
Order By: Relevance
“…Pezzati et al 6 and Bokiniec et al 8 , reported that there was no difference in CBFV in both brain hemispheres in healthy term neonates. Assis, et al 13 described no significant difference in RI between right and left ACA and MCA in a group of 45 preterm healthy newborns.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Pezzati et al 6 and Bokiniec et al 8 , reported that there was no difference in CBFV in both brain hemispheres in healthy term neonates. Assis, et al 13 described no significant difference in RI between right and left ACA and MCA in a group of 45 preterm healthy newborns.…”
Section: Discussionmentioning
confidence: 95%
“…Studies has shown that there was no correlation between the mean blood pressure and mean blood flow velocity in cerebral arteries, and that this change is likely to represent a normal adaptive response of the cerebral circulation to postnatal life, when the efficiency of the CBF autoregulatory response in general improved with increasing age and maturity of the brain 6,25 . In the 50 full term healthy newborns studied between 12h and 72h of life, the results showed not statistically differences on CBFV, PI and RI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Baseado em tais evidências, o presente estudo foi concebido com o objetivo de avaliar a velocidade de fluxo sanguíneo cerebral (FSC) através do mó-dulo Doppler realizado entre 24-48 horas de vida e a possível associação com algumas variáveis maternas e perinatais em RN a termo PIG, comparando os resultados com aqueles obtidos em RN adequados para idade gestacional (RN AIG), com a finalidade de utilizá-lo futuramente como instrumento de predição do risco no período neonatal para alterações no território vascular cerebral correspondente e o prognóstico neurológico em médio e longo prazo. As ACA e ACM foram localizadas anatomicamente pelo módulo bidimensional do ultra-som e detectadas as ondas de fluxo sanguíneo através do módulo de Doppler pulsado 9 . A ACA foi visualizada através da janela transfontanelar anterior, na região pericalosa e a ACM foi aferida na região temporal, ao nível do polígono de Willis.…”
unclassified